Anti-malarial IgG subclasses pattern and FcγRIIa (CD32) polymorphism among pregnancy-associated malaria in semi-immune Saudi women - Nasr, Amre (BioMed Central, 2013)
BACKGROUND: Pregnant women remain are at an increased risk of malaria with primigravidae being at the highest risk. Genetic polymorphism of the Fc receptor IIa for immunologlobulin (Ig) G (FcγRIIa) determines IgG subclass binding. Protection against pregnancy-associated malaria (PAM) is associated with the production of IgG specific for apical membrane antigen-1 (AMA-1). The present study was undertaken to examine the relationship between specific IgG/IgG subclasses and malaria infection. The second aim of the study is to examine the association between FcγRIIa R/H131 polymorphism in correlation with specific anti-malarial IgG antibodies of AMA-1 distribution and asymptomatic malaria infection among Saudi women living in the southern part of Saudi Arabia. METHODS: One hundred and twenty pregnant women living in an area of meso-endemic Plasmodium falciparum malaria infection were consecutively enrolled onto the study. These pregnant women were asymptomatic and attending routine antenatal clinics. The levels of plasma antibodies (IgG and subclasses AMA-1) were measured using indirect enzyme-linked immunosorbent assays (ELISA). Genotyping of FcγRIIa-R/H131 dimorphism was performed using gene-specific polymerase chain reaction (PCR) amplification with allele-specific restriction enzyme digestion (BstU1) of the PCR product. RESULTS: A total of sixty-two (52%) pregnant women was diagnosed with asymptomatic malarial infection (ASM) compared with 58 (48%) malaria free controls (MFC). In the ASM group, there were high levels of anti-malarial IgG1 and IgG3, when compared to MFC (P value <0.001, respectively). The FcγRIIa-R/R131 genotype and R131 were found to be statistically significantly more prevalent in the ASM group when compared to the MFC group [55% for ASM versus 12% for MFC, odds ratio (OR) 5.62, 95% confidence interval (CI)= (2.03- 15.58), P value= 0.001]. However, the H/H131 genotype showed statistically significant association with MFC [14% for ASM versus 50% for MFC, OR(0.36), 95% CI= (0.14- 0.95), P value= 0.03]. CONCLUSIONS: The study revealed that the ASM patients had higher anti-malarial IgG and IgG subclasses antibody levels when compared to the MFC. The FcγRIIa-R/R131 genotype and R131 allele were found to be statistically prevalent in the ASM when compared to the MFC group. The individuals carrying H/H131 were consistently associated with higher levels of anti-malarial IgG subclasses.